Importance of Inscriptions in Historiography of Rajasthan - Tripathi, Rahul (International Journal of Social Sciences and Management, 2016)
Historiography is the area of study which emphasizes on the writing of history. Various sources are available which enable the historian to study and analyze the contemporary political and social conditions. Amongst these, inscriptions form an important component, especially when we talk about Rajasthan. There are various inscriptions which are scattered all over Rajasthan and which, if studied thoroughly, may be of immense importance. The details of some rare inscriptions of Rajasthan have been compiled so as to make the study relevant. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 5-7